Flexible grant schemes: a systematic scoping review - Klepac, B.; Mowle, Amy; Fitzpatrick, E.; Craike, M. (BioMed Central, 2025)
Background Governments can take a range of approaches to funding public health initiatives. One way is through grant-making to other organisations to support the delivery of programs, projects, services, or activities. There is a growing interest in non-traditional approaches to grant-making, including flexible grant schemes. While there is no universally accepted definition of flexible grant schemes, they are commonly understood as granting models that are, unlike traditional granting models, designed to be adaptable to the needs of grantees by allowing them more f lexibility in the use of funds, project timelines or objectives. Interest in flexible grant schemes is, in part, a response to criticisms of traditional granting models that are often deemed inadequate to support multi-sectoral and placebased responses to complex public health problems. To the best of our knowledge, there have been no attempts to map the available evidence on flexible grant schemes. Therefore, this systematic scoping review aimed to explore the literature on flexible grant schemes, interpretations of flexibility across the grant schemes, the extent to which and how grant schemes have been evaluated, and key factors associated with the perceived success of grant schemes. Methods A systematic search of academic and grey literature was conducted through eight databases. We followed a widely used five-phase methodological framework for scoping reviews and utilised PRISMA-ScR Checklist to enhance the methodological rigour of the review. Results Out of 10,368 screened documents, 38 publications met the inclusion criteria. Fourteen of the 38 publications were related to public health, and 28 were published after 2010. We found a lack of clarity and consistency in the interpretation of flexibility in the included studies. Three dominant, interrelated themes were identified: adaptation, autonomy, and coordination. Five publications were self-described as evaluations, a range of service-level or infrastructure outcomes were examined, and findings were generally positive. Seven factors were identified as being associated with the perceived success of flexible grant schemes: collaboration and partnership building, staff capacity, clear and effective communication, alignment among diverse stakeholders, uncertainty, accountability, and administrative burdens. Conclusion We found that the number of publications on flexible grant schemes has substantially increased since 2010. Although interest in flexible grant schemes has increased, there is a lack of clarity and inconsistent interpretations of ‘flexibility’. We suggest greater clarity in grant guidelines to improve communication and alignment across grantees and funders. The capacity of grantees and funders to implement and administer flexible grant schemes was identified as critical to their success, suggesting that investment in capacity development is needed.